2010
DOI: 10.1111/j.1440-1754.2009.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infections in Central Australia

Abstract: In the arid, desert region of Central Australia, RSV infection occurs throughout the year, but is more frequent in winter and more common in Aboriginal children. These data are important for understanding RSV epidemiology in desert regions, and for planning active or passive RSV immunoprophylaxis in these and other similar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…Interestingly, our three consecutive years of observation showed the peak of RSV disease always occurred in the dry hot season. This endemic pattern is distinct from that in countries in the temperate zone, where RSV outbreaks normally occur during the winter season [9,18,20]. We found that influenza virus was the second most important virus causing paediatric ARI hospitalisations and circulated throughout the year in this area without a clear peak.…”
Section: Rsv As Leading Viral Pathogen Causing Ari Hospitalisation Inmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, our three consecutive years of observation showed the peak of RSV disease always occurred in the dry hot season. This endemic pattern is distinct from that in countries in the temperate zone, where RSV outbreaks normally occur during the winter season [9,18,20]. We found that influenza virus was the second most important virus causing paediatric ARI hospitalisations and circulated throughout the year in this area without a clear peak.…”
Section: Rsv As Leading Viral Pathogen Causing Ari Hospitalisation Inmentioning
confidence: 80%
“…Viruses also play critical roles in the development of ARI or pneumonia in young children. However, elucidating the roles of viral pathogens may be complex as a wide range of viruses, such as respiratory syncytial virus (RSV), human rhinovirus (HRV), influenza virus (FLU) A and FLU B, parainfluenza virus (PIV) and human metapneumovirus (hMPV), are associated with severe forms of childhood ARI including bronchiolitis and pneumonia [5][6][7][8][9]. A systematic review has estimated that 22% of severe ARI episodes among children are related to RSV infections [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty‐four studies from 26 countries that were published between 2002 and 2014, with RSV‐associated ARI hospitalization rates for community‐acquired, medically attended, laboratory‐confirmed severe RSV‐ARI in children <5 years of age, were included in the incidence analysis. The incidence estimates of RSV‐associated ARI hospitalization (per 1,000 children per year) were stratified according to age and region (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Within Australia, RSV infections in Alice Springs, Central Australia (23.7°S) occur throughout the year, but peak in winter; which is a typical Southern Australian pattern and similar to the Central Australian winter influenza season. A high burden of RSV disease in Indigenous compared to non‐Indigenous infants has been previously described .…”
Section: What This Paper Addsmentioning
confidence: 87%